Characterization of endophytic bacteria from selected banana and their potential in controlling fusarium wilt in Northen Tanzania - Musa, F. (University of Dar es Salaam, 2023)
Fusarium wilt is one of the devastating phytopathogen diseases hindering banana production worldwide. This study aimed at characterising endophytic bacteria with the potential to control Fusarium wilt from selected local bananas. Endophytic bacteria were isolated from root and corm, grouped based on morphological features and identified using the 16s rRNA gene. Identified endophytic bacteria were challenged with Foc in vitro and in vivo. Out of 409 endophytic bacteria isolated, 12 isolates showed the potential to control Foc in vitro. Those endophytic bacteria were Bacillus amyloliquefaciens strain LM2303, Pseudomonas protegens strain E2HL9, Bacterium strain BS117, Enterobacter sp. strain LMRE105, Klebsiella aurignosa, Kluyvera sp. strain GS4, Kosakonia oryzae, Pseudomonas sp. strain CHP03, Pseudomonas sp. strain 2-31, Pseudomonas kribbensis strain WTB15, Pseudomonas sp. strain CPF-2 and Sphingomonas paucimobilis strain AIMST S2. Among the 12 isolates, the in vitro test Area Under Disease Progress Curve (AUDPC) of Pseudomonas protegens was the lowest (5.19 ± 0.66) followed by Bacillus amyloliquifaciens (7.30 ± 0.74), while the control was 14.74 ± 0.31. These two endophytic bacteria (P. protegens and B. amyloliquefaciens) that showed the highest potential to control Foc in vitro were subjected to in vivo tests using sterile tissue culture banana seedlings. B. amyloliquefaciens reduced the disease severity by 32.1%. This study contributes to understanding the diversity of endophytic bacteria in banana plants and their potential to control Foc. Therefore, more studies are recommended to research other banana varieties to have a complete picture of the endophytic bacteria diversity and to explore the mechanism used by endophytic bacteria to manage Foc disease.